2018
DOI: 10.4081/jbr.2018.7437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rate of Klebsiella pneumoniae in the intensive care unit: epidemiology and molecular characteristics

Abstract: Klebsiella pneumoniae carbapenemase producing bacteria are defined as a group of Gramnegative bacilli that are highly resistant to drugs. The resistance of pathogens of the Enterobacteriaceae family to β-lactam antibiotics such as carbapenems is considered a major threat in the medical field. The main aim of the current study was to explore and confirm the occurrence of carbapenemase producing K. pneumoniae in the Intensive Care Unit (ICU) in different hospital environment sample sites of two Egyptian hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This nding was similar to that observed in Egypt, where the Klebsiella pneumoniae isolated from several ICUs were found more in beds, bedside tables, suction tubes, and ventilator tubes. [12] However no Klebsiella pneumoniae was isolated from the ICU in this study. This variation in the detection of the organisms from the ICUs of the different hospitals could be attributed to the maintenance of strict infection control measures in the ICU of NAUTH, Nnewi.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This nding was similar to that observed in Egypt, where the Klebsiella pneumoniae isolated from several ICUs were found more in beds, bedside tables, suction tubes, and ventilator tubes. [12] However no Klebsiella pneumoniae was isolated from the ICU in this study. This variation in the detection of the organisms from the ICUs of the different hospitals could be attributed to the maintenance of strict infection control measures in the ICU of NAUTH, Nnewi.…”
Section: Discussionmentioning
confidence: 70%
“…Contrasting ndings were observed in an Egyptian study which revealed 100% resistance to Meropenem. [12] The reduced rates of resistance to the carbapenems in this study could be attributed to the limited use of carbapenems due to the high cost of purchase of these antibiotics in the country.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation